Kolaboratif Pengelolaan Candi Borobudur dalam Penanggulangan Bencana Gunung Merapi - Pratikno, Hendro; Kurniadi, Anwar (Edukasi IPS, 2021)
Mount   Merapi   is   one   of   the   most   active   volcanoes   in   Indonesia,   which   is administratively located in Sleman Regency and Magelang Regency in the Central Java Province. The Borobudur Heritage Conservation Center in Magelang Regency does not yet have a  tandard Operating  Procedure  (SOP)  for  cleaning  the  temple  from  volcanic  ash, and  not  clear  who  is  the responsibe for it. If the condition is allowed, I could be bad impact on the safety and preservation aspects. The  purpose  of  this  study  was  to  know  how  far  the  collaboration  among  stakeholder  in managing of the Borobudur temple. This study usedqualitative research methods withdescriptive design. The  results  showed; 1)   dialog among stakeholders didn’t find the solution; 2) buliding trust  with  making  program  Twin  Villages  espescially  among  villages  that  impacted  by  Merapi Mount eruption; 3) commitment to made program of structural anda non structural mitigation and also  preparedness;  4)  sharing  understanding  with  making  communication and  collaboration  and synergizing  well  patterned  ;  5)  temporary  result  of  the  distribution  of  authority  was  still  not optimal  so  that  it  was  impotant  to  make  new  official  regulation.   Theconclusian  showed thecollaboration  among  stakeholders  were  still  not  optimal  so  it  needed  to  make  new  offiscial regulation. Recomendation was to among manager stakeholders make it round table to determine new regulation on ministeri level as well as field level (Standard Operational Procedure/SOP).